Mineralogical and geochemical analysis of sodium bentonites in continental settings: The Uspallata Group (Triassic) of the Cuyana Basin, Mendoza province, Argentina. (October 2020) - Salduondo, Joaquín; Comerio, Marcos; Cravero, Fernanda; Etcheverry, Ricardo
Abstract: The Triassic Uspallata Group of the Cuyana rift Basin is characterized by continental deposits including alluvial, fluvial and lacustrine systems, mainly composed of volcaniclastic (reworked) and pyroclastic sediments. The present work focuses on the ash fall tuffs levels (bentonites) in order to understand the origin of their sodium composition since classic worldwide natural sodium bentonites link with marine environments as a source of sodium. The mineralogical attributes and relationship with diagenetic alterations have been explored by petrography, X-ray diffraction, and geochemical analysis. The tuff levels, recorded in the Cerro de las Cabras, Potrerillos and Cacheuta formations, provide the most reliable representation of the composition of the original material and diagenetic alterations due to these levels are devoid of detrital input. Accordingly, they represent key elements to explore the origin of huge bentonite deposits in the basin. In the study units, Na-montmorillonite and analcime, found at concentrations of up to or more than 50 vol%, grew at the expense of vitric components and represent authigenic minerals developed under early diagenesis. Following sedimentological and paleogeographic evidence the alteration of volcanic glass occurred in hydrologically open lacustrine systems that reached saline-alkaline conditions. The changes in the (Na + K)/H + ratio influenced the formation of Na-montmorillonite and analcime through the succession. In addition, kaolinite is an important alteration mineral that fills cavities, replaces the feldspar grains, and probably the early diagenetic minerals. The origin of kaolinite is due to the combined effects of decomposition of organic matter and incursion of meteoric freshwater during late-stage telogenesis which generated the acidification of pore waters. Based on geochemical proxies, geochronological data and the geodynamic context the input of high volumes of pyroclastic material may thus be the result of explosive volcanism from an arc-subduction complex located to the west at these latitudes. The present work suggests that the composition of Na-rich pyroclastic ashes accumulated in hydrologically-open lake systems which conditioned the formation of sodium bentonites in continental settings. Highlights: The Triassic Uspallata Group of the Cuyana rift Basin has Na-bentonite deposits. Pyroclastic ashes accumulated in hydrologically-open lake systems. Na-montmorillonite, analcime and kaolinite are the most important authigenic minerals. Active volcanism at a convergent plate margin in the western part of Gondwana as the source of pyroclastic material.